Efforts to increase the learning motivation of Class XI-MBA students with art exhibition materials through Artsteps Media - Febriani Wulandari; Ike Ratnawati; Shinta Adhisti Oktarini (Humanities Horizon, 2026)
The main problem is that students are less motivated to learn because the material is theoretical, tends to be monotonous, boring, and uninteresting. Using Artsteps Media, this project aims to improve the learning motivation of class XI-MBA students at SMA Negeri 4 Malang to learn about art and culture. Classroom Action Research (CAR), developed by Kemmis and McTaggart, was used in this study. This study was conducted in two cycles with four stages, namely planning in the first stage, action in the second stage, observation in the third stage, and reflection in the fourth stage. A total of 35 students participated in the activity. Data collection methods include observation, interviews, performance tests, and documentation. Based on the results of the study, students' learning motivation increased in pre-cycle from 29% to 100% in cycle II. By depicting a virtual exhibition space, the use of Artsteps Media can make learning more interesting and encourage students to participate more actively. This study shows the effectiveness of using Artsteps Media in improving students' learning motivation in studying art and culture with art exhibition materials.